Gravitational p → ∆+ transition form factors in chiral perturbation theory - H. Alharazin; B.-D. Sun; E. Epelbaum; J. Gegelia; U.-G. Meißner (Journal of High Energy Physics, 2024)
Abstract The gravitational form factors of the transition from the proton to the ∆+ resonance are calculated to leading one-loop order using a manifestly Lorentz-invariant formulation of chiral perturbation theory. We take into account the leading electromagnetic and strong isospin-violating effects. The loop contributions to the transition form factors are found to be free of power-counting violating pieces, which is consistent with the absence of tree-level diagrams at the considered order. In this sense, our results can be regarded as predictions of chiral perturbation theory.